Nuclease-Resistant DNA via High-Density Packing in Polymeric Micellar Nanoparticle Coronas - Rush, Anthony M; Thompson, Matthew P; Tatro, Erick T; Gianneschi, Nathan C (ACS nano, 2013)
Herein, we describe a polymeric micellar nanoparticle capable of rendering nucleic acids resistant to nuclease digestion. This approach relies on utilizing DNA as the polar headgroup of a DNA–polymer amphiphile in order to assemble well-defined, discrete nanoparticles. Dense packing of DNA in the micelle corona allows for hybridization of complementary oligonucleotides while prohibiting enzymatic degradation. We demonstrate the preparation, purification, and characterization of the nanoparticles, then describe their resistance to treatment with endo- and exonucleases including snake-venom phosphodiesterase (SVP), a common, general DNA digestion enzyme.